COMPUTATIONAL STUDY OF ARYL TRANSFER REACTION MECHANISM FROM OXYGEN TOWARDS NITROGEN CATALYZED BY ACRIDINIUM ION - Khwarizmi Syuhada, Nabil
Benzene is an organic compound bearing a uniqueness from aromaticity. The uniqueness of benzene results in ubicity on its derivatives, for example Trp-Cage and self-healing polymer. The reaction regarding of the aryl functional group tends to be difficult to occur because the high energy requirement in the dearomatization process. In the presence of a photocatalyst, aryl migration is possible in a relatively mild condition. In this research, the mechanism of aryl transfer reaction from oxygen towards nitrogen of 2-phenoxyethane-1-amine to 2- (phenylamino) ethane-1-ol has been studied. The mechanism was proposed by the previous studies and it is now proven by computational method using composite-methode based on DFT (density functional theory) termed r2SCAN-3c. The result is the proposed mechanism was partially refuted and a new alternatif is necessary regarding the proton migration step. One of the alternative path way is that the proton transfer is catalysed by the reactant and it has already been computed.